The Implications of Equity Issuance Decisions within a Parent-Subsidiary Governance Structure - Slovin, Myron B.; Sushka, Marie E. (Journal of Finance, 1997)
We provide evidence about the motivation for a parent–subsidiary governance structure by analyzing valuation effects of seasoned equity offerings by publicly traded affiliated units. Our results support Nanda's (1991) theoretical model which predicts equity offerings convey differential information about subsidiary and parent value. Subsidiary equity issuance has negative valuation effects on issuing subsidiaries and positive effects on parents, while parent equity issuance reduces issuing parent wealth and increases subsidiary wealth. Our evidence suggests that a parent–subsidiary organizational structure enhances corporate financing flexibility and mitigates underinvestment problems identified by Myers and Majluf (1984). There is no evidence of subsidiary wealth expropriation.